Intravascular mesenchymal stromal/stem cell therapy product diversification: time for new clinical guidelines - Moll, Guido; Bieback, Karen (Trends in molecular medicine, 2019)
Intravascular infusion is the most popular route for therapeutic multipotent mesenchymal stromal/stem cell (MSC) delivery in hundreds of clinical trials. Meta-analysis has demonstrated that bone marrow MSC infusion is safe. It is not clear if this also applies to diverse new cell products derived from other sources, such as adipose and perinatal tissues. Different MSC products display varying levels of highly procoagulant tissue factor (TF) and may adversely trigger the instant blood-mediated inflammatory reaction (IBMIR). Suitable strategies for assessing and controlling hemocompatibility and optimized cell delivery are crucial for the development of safer and more effective MSC therapies.
Gesehen am 26.11.2019